Malcolm Sawyer claims advocates of full reserve banking are “cranks”. - Musgrave, Ralph Stephen (Advances in Social Sciences Research Journal, 2019)
Giuseppe Fontana and Malcolm Sawyer (F&S) penned a paper published in the Cambridge Journal of Economics entitled “Full Reserve Banking: More ‘Cranks’ Than ‘Brave Heretics’” (Fontana and Sawyer (2017). The paper basically argued against full reserve banking. The purpose of the paper below is to show that the F&S paper is riddled with errors. The F&S paper was answered in the Cambridge Journal of Economics by Dyson, Hodgson and van Lerven (2016)). The latter paper was by its own admission limited in scope: it addressed just four points made by F&S. The paper below enlarges on the latter paper: i.e. the paragraphs below point to the errors in F&S’s paper missed by or not dealt with by Dyson & Co (21 errors to be exact). The paper below deals with each error as it occurs. Errors are numbered. Some of the errors are serious, which raises the question as to who the “cranks” are. Another question that arises is: what is a respectable economics journal like the Cambridge Journal of Economics is doing publishing this defective material? I.e. it raises the question as to whether respectable economics journals are really any better than “non-establishment” journals like Advances in Social Sciences Research Journal. The paper below was not submitted first to the above Cambridge journal because they place a 1,500 word limit on papers which comment on other papers, and 1,500 words is nowhere near enough to deal with the numerous errors made by F&S.